A Rare Case of Systemic Lupus Erythematosus Applying to the Family Medicine Outpatient Clinic with Periorbital Edema - Arpa, Tuğba; Kutan Fenercioğlu, Ayşen; Turfaner Sipahioğlu, Nurver (Cerrahpaşa Medical Journal, 2021)
Systemic lupus erythematosus may present with different clinical signs such as fatigue, fever, dermatitis, photosensitivity, alopecia, arthritis, serositis, hematological abnormalities, mucosal ulcerations, Raynaud phenomenon, neurological disease, and glomerulonephritis. Rarely, kidney involvement with the absence of antinuclear antibody (ANA) positivity may be the first and only finding in systemic lupus erythematosus. Since renal involvement affects prognosis negatively, delays in diagnosis and treatment can cause an increase in mortality and morbidity. In this article, we presented an interesting case of systemic lupus erythematosus, who applied to the family medicine outpatient clinic with periorbital edema in whom we considered renal involvement and determined histopathological findings that were compatible with lupus nephritis despite the absence of ANA positivity. Cite this article as: Kutan Fenercioğlu A, Turfaner Sipahioğlu N, Arpa T. A Rare Case of Systemic Lupus Erythematosus Applying to the Family Medicine Outpatient Clinic with Periorbital Edema. Cerrahpaşa Med J 2021; 45(1): 43-48.